SYSTEMATIC LITERATURE REVIEW: KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN IPS SEKOLAH DASAR - Mulyati, Sri; Rosidah, Ani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Critical thinking skills are recognized as a core competency in the 21st century that must be fostered from elementary school, particularly through Social Studies (IPS). Social studies learning offers a contextual nature that enables students to analyze social phenomena, understand cause-and-effect relationships, and make rational decisions. However, various studies indicate that elementary school students' critical thinking competencies in social studies learning have not yet developed optimally. This study aims to examine students' critical thinking competencies in social studies learning in elementary schools by referring to previous literature. The method used was a Systematic Literature Review (SLR) following the PRISMA protocol. Reference searches were conducted through the Google Scholar and Publish or Perish platforms with publications spanning 2020-2025. Based on inclusion and exclusion criteria, ten articles were obtained and processed through thematic analysis. The study findings revealed that elementary school students' critical thinking competencies were generally in the moderate category, with analysis, evaluation, and conclusion-drawing indicators being the weakest aspects. These competencies are influenced by several factors originating from within the students and the educational environment. Furthermore, implementing learning approaches that make students the primary actors in the learning process, such as problem-based learning and discussion, has proven effective in improving critical thinking skills in social studies. This study contributes to a comprehensive mapping of students' critical thinking skills and recommends social studies learning strategies that can be utilized by elementary school teachers.